Relationship of Vehicle Factors as Causing Factors of Severity of Tanker Car Accidents at PT XYZ in 2022-2023 - Renaldi, Josua Readus; Tejamaya, Mila (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The three main risk factors causing traffic accidents are categorized into human factors, vehicle factors and environmental factors (Haddon, 1972). This study aims to analyze vehicle factors as the cause of fuel tanker car accidents at PTXYZ during the period 2022–2023 and their relationship to severity. The unit of analysis for this study was 33 investigation reports as secondary data. Univariate analysis was carried out on the description of vehicle factors including: car age, preventive maintenance, pre-trip inspection, braking system, tire condition, electricity, lighting/visibility, and modification, as well as multivariate analysis of ordinal logistic regression to determine the relationship between vehicle factors and vehicle severity (Category N–A), humans (fatal, serious injury, minor injury), and the environment (fuel spill). This study found that the dominant vehicle risk factors and severity were braking system failure (60%), accident severity without injury dominated (81.8%). Most incidents did not result in spills, but 6.1% were fatal. The results of the multivariate analysis indicate that although no vehicle factors are statistically significant at the 95% confidence level, factors such as braking system, steering, tires, engine, and visibility have high positive estimates indicating a tendency to increase crash severity. The findings highlight the need to focus on brake system inspection and maintenance, as well as improve training programs and telemetry monitoring. Recommendations include strengthening preventive maintenance, sharpening pre-trip inspection, and conducting further research with a larger sample to validate the results.